Dementia Care Class Increases Confidence of Informal Caregivers in Community-Based Dementia Care - Ashri Maulida Rahmawati; Muhamad Jauhar; Diana Tri Lestari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Dementia develops rapidly each year in line with the increasing number of the world's elderly population. Dementia causes dependence, reduced quality of life, and even disability. Currently, the focus of treatment is carried out by health workers. There is a need for an informal caregiver capacity-building program in community-based dementia care. This study aimed to identify the effect of community based dementia care class on self-confidence among informal caregiver. This study used a pre-experimental pre and post-test with control group design. Sample choosen with purposive sampling consisted of 24 informal caregivers for each intervention and control group. The research instrument used Self-Confidence Questionnaire about Dementia Care Skills with a reliability value of 0.947. The intervention given 4 sessions in 2 days with 45-60 minutes per session.  Data analysis used paired t-test and independent t-test. The results showed that there was an effect of dementia care class on the confidence of informal caregivers in community-based dementia care with a value of p=0.000 (p less than 0.05). These learning models and media can be integrated into elderly posyandu and elderly health programs in healthcare facilities in community-based dementia management. Abstrak: Demensia berkembang pesat setiap tahunnya seiring dengan bertambahnya jumlah penduduk lanjut usia di dunia.Demensia menyebabkan ketergantungan, penurunan kualitas hidup, bahkan kecacatan. Saat ini, fokus pengo batan dilakukan oleh tenaga kesehatan. Ada kebutuhan untuk program peningkatan kapasitas caregiver informal dalam perawatan demensia berbasis masyarakat. Penelitian ini bertujuan untuk mengidentifikasi pengaruh kelas perawatan demensia terhadap kepercayaan diri pada caregiver informal dalam perawatan demensia berbasis komunitas. Penelitian ini menggunakan pre-experimental pre and post-test with control group design. Sampel dipilih dengan purposive sampling terdiri dari 24 caregiver informal untuk masing-masing kelompok intervensi dan kontrol. Instrumen penelitian menggunakan Self-Confidence Questionnaire tentang Dementia Care Skills dengan nilai reliabilitas 0,947. Intervensi diberikan 4 sesi dalam 2 hari dengan durasi 45-60 menit per sesi. Analisis data menggunakan uji t berpasangan dan uji t independen. Hasil penelitian menunjukkan bahwa ada pengaruh kelas perawatan demensia terhadap kepercayaan diri caregiver informal dalam perawatan demensia berbasis komunitas dengan nilai p=0,000 (p kurang dari 0,05). Model dan media pembelajaran ini dapat diintegrasikan ke dalam posyandu lansia dan program kesehatan lansia di fasilitas kesehatan dalam penanganan demensia berbasis komunitas.